2005
DOI: 10.1021/ac048147m
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Mode of Action of Antibiotics Using Raman Spectroscopy:  Investigating Subinhibitory Effects of Amikacin on Pseudomonas aeruginosa

Abstract: During the last 20 years the rate at which new antimicrobial agents are produced has decreased dramatically, with concomitant increase in the number of pathogens that are becoming multidrug resistant. Together these have created a patient healthcare risk and this is of great concern. A crucial aspect for the discovery of new antibiotics is the development of new techniques that allow rapid and accurate characterization of the mode of action of the pharmacophore. In this work UV resonance Raman (UVRR) spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
66
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 38 publications
4
66
0
1
Order By: Relevance
“…Raman spectroscopy has been used with a similar excitation wavelength to study the effects of the protein synthesis inhibitor amikacin on Pseudomonas aeruginosa. As the concentration of amikacin was increased, the intensity of protein-related Raman peaks decreased, whereas the intensity of nucleic acid bands increased, consistent with the mechanism of action of amikacin (29). Similar results were reported, as Raman spectroscopy was used to monitor the relative protein and DNA content of individual E. coli cells treated with cefazolin (18).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Raman spectroscopy has been used with a similar excitation wavelength to study the effects of the protein synthesis inhibitor amikacin on Pseudomonas aeruginosa. As the concentration of amikacin was increased, the intensity of protein-related Raman peaks decreased, whereas the intensity of nucleic acid bands increased, consistent with the mechanism of action of amikacin (29). Similar results were reported, as Raman spectroscopy was used to monitor the relative protein and DNA content of individual E. coli cells treated with cefazolin (18).…”
supporting
confidence: 82%
“…The authors found the resulting Raman spectra contained spectral features suggesting higher lipid and RNA content and lower cytochrome content in E. coli harboring the plasmid. In addition, Raman spectroscopy has been used to monitor the metabolic state under antibiotic stress (18,(27)(28)(29). For example, Neugebauer et al (28) used Raman spectroscopy with a 244-nm excitation wavelength to track the ratio of protein to nucleic acids during the growth of Bacillus pumilus treated with ciprofloxacin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria can be identified within 6 h by Raman spectroscopy and 8 h by infrared spectroscopy (9,22,29). Recently, these spectroscopic methods have been intensively applied to study bacterial injury and inactivation by various treatments, such as bacteriocin (8), antibiotics (28,33,40), heat (3,4), and sonication (27). Infrared spectroscopy is useful for bulk bacterial detection (the detection limit is ϳ10 4 to 10 5 CFU/ml) (12), while Raman spectroscopy can potentially detect single bacterial cells (46), especially when a nanosubstrate is employed to signal enhancement, a technique called surface-enhanced Raman spectroscopy (SERS) (13).…”
mentioning
confidence: 99%
“…The selected unrelated principal components (PCs) are plotted and visualized in cluster forms (18). DFA can construct branched dendrogram structures using prior knowledge of the composition of a biological sample (28). SIMCA is a supervised classification method.…”
mentioning
confidence: 99%